The Threat Divider: Expanding the Role of the Military in Climate Change Adaptation - Badichek, Gregg (Columbia Journal of Environmental Law, 2019)
It is all but undeniable that climate change creates drastic national security concerns for the United States, despite the assertions of certain contrary political forces. While the United States legislature and judiciary can and should play a direct role in addressing these risks by abrogating climate risk, the executive branch and its agencies, in comparison, possess tremendous opportunities and abilities to do so. Specifically, the armed forces under the DoD face unique challenges, but also possess unique advantages, in the realm of climate change adaptation. Certainly the military divisions under the executive play a paramount role in hemming national security risks; due to its developing expertise, the possibility of the military’s enormous influence in the realm of climate change adaptation should be recognized and embraced. This Note argues that the military’s role in climate change adaptation—specifically in regards to national security threats domestically and abroad—should be embraced and expanded as adaptation efforts become increasingly necessary.